1974
DOI: 10.1177/030098587401100308
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Basement Membrane Thickening in Rhesus Monkeys

Abstract: Abs tract. T hicke ned hyalin e tr ache al membra ne simila r to that which occurs with severa l respira to ry co nditions in man was seen in Rhe su s mo nkeys. Th e memb ran e was cosinophili c a nd up to 50.4 urn thic k. Freq uentl y eosino phils a nd ma st ce lls were seen in the trach ea l mucosa a nd submucos a. Us ing fluore scent microscop y, IgG, B 1C, B1A a nd a lbumin were identifi ed in the membran e. Electro n microscop y sho wed tha t the membra ne was co mposed of I8.8-nm co llage n-like fibr ils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One study of rhesus monkeys suggested that thickened basement membranes were an abnormal feature and demonstrated deposition of IgG, complement components, and albumin in them (Splitter et al, 1974). These results were based on examination of 90 otherwise healthy monkeys, 72 of which had basement membranes greater than 7 pm in thickness.…”
Section: Discussionmentioning
confidence: 99%
“…One study of rhesus monkeys suggested that thickened basement membranes were an abnormal feature and demonstrated deposition of IgG, complement components, and albumin in them (Splitter et al, 1974). These results were based on examination of 90 otherwise healthy monkeys, 72 of which had basement membranes greater than 7 pm in thickness.…”
Section: Discussionmentioning
confidence: 99%